The Legal Binding Power of the State Administrative Court's Decision In the 2024 General Election - Nursidi, Didi; Suneri, Suneri; Suhendar, Suhendar (Universitas Wiralodra, 2025)
In the case of Irman Gusman, the KPU RI cq KPU West Sumatra did not implement the Jakarta PTUN decision, but on the other hand carried out the interlocutory decision of the Constitutional Court of the Republic of Indonesia to implement the PSU by including Irman Gusman so that even though the person concerned obtained the fourth most votes, but because he had been crossed out in the DCT of the Candidate for DPD Member of the West Sumatra Dapil, Irman Gusman was declared Failed to Qualify as an Elected DPD Member. This incident shows the complexity of the interests in the legal process which is inconclusive in the administration of the electoral system in Indonesia. For this reason, the problem is formulated as follows: (1) How is the legal binding force of the decision of the State Administrative Court that is qualified as non-executable?; (2) How is the execution of the decision of the State Administrative Court Number: 600/G/SPPU/2023/PTUN. JKT. which is non-executable? In this study , a descriptive method with a juridical-normative approach is used, and the data is analyzed qualitatively by emphasizing the use of applicable laws and regulations, expert opinions and research results.The results of the study show that: (1) As long as the judge's decision is not canceled, then as long as the decision remains legally binding even though it cannot be implemented (Non-Executable); (2) PTUN Decision Number: 600/G/SPPU/2023/PTUN. JKT cannot be carried out because the KPU RI Cq KPU West Sumatra adheres to the Election Stages that have been set